PENGARUH TRUST, COMMITMENT, COMMUNICATION, EMPATHY TERHADAP CUSTOMER LOYALTY PADA MAKMU KAFE SURABAYA - Redina Isnu Putri; Dudi Anandya; Indarini Indarini (CALYPTRA, 2018)
This research purpose is to know the influence of trust, commitment, communication, and empathy toward Customer Loyalty. Object that taken is Makmu Kafe Surabaya. Data that is used on this research is primary data which obtained by questioner spread. The respondent in this research is 200 respondents who once visit and taste food at “Makmu Kafe Surabaya” at least twice in 6 last months. Sample obtaining technique in this research is non probability sampling. This research uses quantitatif approach through statistic experiment. The experiment has done by using Structural Equation Modeling (SEM) method. The research result reveals that trust gives positive influence toward customer loyalty, commitment gives positive influence toward customer loyalty, communication gives positive influence toward customer loyalty, empathy gives positive influence toward customer loyalty.